DNA extraction, Polymerase Chain Reaction, and Sequencing : Workshop in Clinical Genetics - Sumadi Lukman Anwar (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
AbstractDNA extraction, Polymerase Chain Reaction (PCR), and Sequencing are basic methods in molecular biology and genetics. Those there are routinely performed as basic methods in genetic research and currently also for diagnostic lab especially for pathology and human genetics. With the advance in the genetics and clinical service for cancer management, mutation analysis is very important not only for diagnosis but also for prediction of therapeutic response. Detection of KRAS, BRAF, EGFR, and c-KIT mutations is presently performed in almost every molecular pathology lab as part of daily clinical service in cancer management. In this workshop we will discuss tips and tricks for those three basic lab methods. How to improve amount and purity of DNA extraction from blood and tissues, how to avoid DNA degradation during the procedure and storage, how to perform PCR, factors and substance that inhibit polymerases during PCR, how to design effective primer pairs, and how basic theory for sequencing, and interpretation of sequencing will be discussed. Although it has been widely discussed, this workshop is especially important for clinicians who previous do not have hands-on laboratory experience. In addition, number of labs with ability to perform and serve basic genetic and molecular analysis are still limited in Indonesia. With this workshop, we expect to improve knowledge and skill in DNA extraction, PCR, and Sequencing.Keywords : DNA, PCR, sequencing